Mathematics Connective Skill Reviewed based on Adversity Quotient on CORE Learning - Konita, Mita; Asikin, Mohammad; Asih, Tri Sri Noor (Unnes Journal of Mathematics Education Research, 2021)
This research aims to describe mathematics connective skill reviewed based on adversity quotient of students on CORE learning model of X graders in learning geometry. This concurrent triangulation mixed method used quantitative data technique by mathematics connective skill test and the qualitative data was obtained by documentation, questionnaire, and interview. The subjects were selected by purposive sampling and consisted of 6 students, each of three students were categorized as camper and climber adversity quotients. The findings showed that different AQ categories would have different mathematics connective skills. It was shown by three climber students met 5 indicators of mathematics connective skills. Meanwhile, 3 camper students met three mathematics connective skill indicators.